2022
DOI: 10.1038/s41598-022-15419-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome doubling enabled the expansion of yeast vesicle traffic pathways

Abstract: Vesicle budding and fusion in eukaryotes depend on a suite of protein types, such as Arfs, Rabs, coats and SNAREs. Distinct paralogs of these proteins act at distinct intracellular locations, suggesting a link between gene duplication and the expansion of vesicle traffic pathways. Genome doubling, a common source of paralogous genes in fungi, provides an ideal setting in which to explore this link. Here we trace the fates of paralog doublets derived from the 100-Ma-old hybridization event that gave rise to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The final event in the genesis of the S. cerevisiae Arf family gene set was duplication of the ancestral Arf1 gene yielding a pair of lineage-specific paralogs (Arf1 and Arf2), which was part of the whole genome duplication (WGD) that occurred in the common ancestor of Saccharomyces and several related genera [24] (Figure 2). Although not the case for S. cerevisiae, taxon-specific expansions of the Arf family by gene duplication have been pervasive across eukaryotes in general.…”
Section: Gene Duplication Also Shapes the Arf Family In A Taxon-speci...mentioning
confidence: 99%
“…The final event in the genesis of the S. cerevisiae Arf family gene set was duplication of the ancestral Arf1 gene yielding a pair of lineage-specific paralogs (Arf1 and Arf2), which was part of the whole genome duplication (WGD) that occurred in the common ancestor of Saccharomyces and several related genera [24] (Figure 2). Although not the case for S. cerevisiae, taxon-specific expansions of the Arf family by gene duplication have been pervasive across eukaryotes in general.…”
Section: Gene Duplication Also Shapes the Arf Family In A Taxon-speci...mentioning
confidence: 99%
“…This domain is composed of GO-BPs such as 'export from cell', 'secretion by cell' and 'exocytosis', which are all vesicle traffic related functions. It has been shown that, as paralogs can be differentially expressed or regulated, or can have different interaction partners, they contribute to the robustness and versatility of the vesicle traffic pathway (Purkanti and Thattai, 2022). In conclusion, GraCoal 2 captures functional redundancy and functional specialisation in GI networks of species with many paralogs.…”
Section: Insight Into the Functions Captured By Gracoalmentioning
confidence: 99%